UTAUT Model Mediated by Government Information System to the Intention to Use of Indonesian Local Government - Hasanah, Dian; Anggiani, Sarfilianty; Usman, Bahtiar (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2024)
Purpose – This study investigates the role of the unified theory of acceptance and use of technology (UTAUT) model on the intention to use mediated by the Government Information System. In the context of this study, the implementation of government information systems through the application of local government information systems (SIPD) in Regional Governments in Indonesia. Methodology/approach –The population in this study includes: Primary High Leadership Officials, Administrator Officers, Supervisory Officers, and SIPD Management ASNs in the Ministry of Home Affairs and local governments with a total sample of 358 respondents. This study uses a form of sampling in the form of purposive sampling and probability sampling, with the sampling technique used in the form of simple random. When viewed from the relationship between variables, this study is included in associative research. The data processing and analysis techniques used in this study were carried out through Descriptive Statistical Tests and Structural Equation Model (SEM). Findings – Based on the results of the study, it is known that Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Condition, either directly or indirectly through the Government Information System as the variable that mediates it, have had an influence on the Intention To use SIPD application. Novelty/value – The novelty of this study fills the research gap by involving the role of the government information system (SIPD) as a mediating factor between performance expectations, effort expectations, social influences, and conditions that facilitate intention to use which is limited only to age and experience as control variables. Thus, a more comprehensive picture of the results of how the influence of factors in UTAUT is mediated by the role of SIPD, and see the extent to which the implications of implementing SIPD in local government can affect the intention to use by civil servants in Indonesia and as recommendations for related parties in developing government information systems.